PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PERTANIAN TANAMAN PANGAN PROVINSI JAWA BARAT - Masluh Masluh Masluh (KarismaPro, 2021)
This study aims to determine and analyze organizational culture and employee performance at the Department of Agriculture and Food Crops, West Java Province, and the influence of organizational culture on employee performance at the Department of Agriculture and Food Crops, West Java Province. Using regression analysis, the research method used is descriptive and verification methods on 74 Department of Agriculture of West Java Province employees. The results showed that in general the organizational culture at the Food Crops Agriculture Service of West Java Province was in a good category. This can be seen from innovation and risk taking, attention to detail, results orientation, people orientation, team orientation, aggressiveness and stability. If viewed from the performance of the employees of the Department of Agriculture, Food Crops, West Java Province, it is in a good category. This can be seen in terms of quality, quantity, timeliness, effectiveness and work commitment which are in the good category as well. Furthermore, organizational culture has a positive and significant influence on employee performance. Kata kunci: Budaya Organisasi, Kinerja